Resurgence of placenta accreta in Indonesia - Rozi Aditya Aryananda (Universitas Airlangga, 2018)
Placenta accreta is a common term used for defining a clinical condition which part or all of the placenta attaches to the myometrium that difficult to remove. Placenta accreta is a placental disorder which has been around for a long time and became a resurgence in Indonesia since 2016 with its incidence reached 2% and is still increasing until now. Placenta accreta is one of the most terrifying conditions faced by gynecologists and resulted in the increase of mortality and morbidity of pregnant women in Indonesia. In the United States, the incidence increased from less than 1 per 2000 pregnancies in 1980 to around 1 per 500 pregnancies until recently. The increased cases of placenta accreta is always directly proportional to the cesarean delivery rates.